2020
DOI: 10.1159/000506334
|View full text |Cite
|
Sign up to set email alerts
|

Differential Diagnosis in Patients with Substance Use Disorder and/or Attention-Deficit/Hyperactivity Disorder Using Continuous Performance Test

Abstract: Background: Although substance use disorders (SUD) and attention-deficit/hyperactivity disorder (ADHD) show significant symptomatic overlap, ADHD is often overlooked in SUD patients. Objective: The aim of the present study was to characterize aspects of attention and inhibition (as assessed by a continuous performance test [CPT]) in SUD patients with and without a comorbid diagnosis of ADHD and in healthy controls, expecting the most severe deficits in patients with a combined diagnosis. Methods: The MOXO-CPT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 58 publications
2
18
0
Order By: Relevance
“…Ginsberg et al [70] found that inmate males with comorbidity of ADHD and SUD conducted more commission responses than psychiatric patients with ADHD alone. The 4 other studies [62, 66, 71, 77] did not find that the presence of ADHD in individuals with substance use was associated with different commission rates compared with individuals with either SUD or ADHD.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…Ginsberg et al [70] found that inmate males with comorbidity of ADHD and SUD conducted more commission responses than psychiatric patients with ADHD alone. The 4 other studies [62, 66, 71, 77] did not find that the presence of ADHD in individuals with substance use was associated with different commission rates compared with individuals with either SUD or ADHD.…”
Section: Resultsmentioning
confidence: 96%
“…Except for the study of Ginsberg et al [70], which found that inmate males with comorbid ADHD and SUD made more omission errors than psychiatric patients with ADHD alone, no study found differences in the rate of omission errors between patients with comorbid ADHD and SUD and patients with either ADHD [62, 66, 71] or SUD [66, 68].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations